A Systematic Review of the Kano Model's Utility in Classifying Healthcare Service Attributes and Driving Patient Satisfaction - Gita Febri Irianti; Sutopo Patria Jati; Cahya Tri Purnami (Universitas Islam Negeri Sumatera Utara, Medan, 2026)
Patient satisfaction is a key indicator of hospital service quality, closely linked to patient loyalty, clinical outcomes, and the reputation of health institutions. However, identifying specific attributes that determine patient satisfaction and dissatisfaction remains a challenge amid the ever-evolving dynamics of healthcare services. The Kano Model offers a useful framework by categorizing service attributes according to their impact on patient satisfaction. This study presents a systematic literature review of the model’s application in hospitals, conducted using the PRISMA protocol. Searches across PubMed, Scopus, and ProQuest for publications from 2019 to 2024 yielded 17 eligible international journal articles, which were analyzed narratively to identify patterns, methods, and findings. Results consistently revealed a hierarchy of patient needs: clinical competence, safety, and accurate information emerged as Must-be attributes, whose absence leads to strong dissatisfaction. Communication quality, responsiveness, and service efficiency were typically One-dimensional attributes, with satisfaction rising proportionally to performance. Digital innovations such as telehealth and personalized services often appeared as Attractive attributes, delighting patients when present but not causing dissatisfaction when absent. . Attribute classification proved dynamic, shaped by clinical context and patient demographics. Furthermore, integrating the Kano Model with frameworks such as SERVQUAL and the Balanced Scorecard enhances strategic prioritization. Several studies also demonstrated that Kano-based interventions can improve both clinical and psychological patient outcomes. Keywords: Patient Satisfaction, Hospital, Kano Model, Service Quality.